2016
DOI: 10.1371/journal.pone.0150567
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Inhibitors in Combination with Erlotinib Demonstrate Enhanced Anti-Tumor Activity in Non-Small Cell Lung Cancer

Abstract: Blockade of epidermal growth factor receptor (EGFR) activity has been a primary therapeutic target for non-small cell lung cancers (NSCLC). As patients with wild-type EGFR have demonstrated only modest benefit from EGFR tyrosine kinase inhibitors (TKIs), there is a need for additional therapeutic approaches in patients with wild-type EGFR. As a key component of downstream integrin signalling and known receptor cross-talk with EGFR, we hypothesized that targeting focal adhesion kinase (FAK) activity, which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…FAK has been verified as the target gene for several other miRs (miR-543 and miR-7) in cancer development [ 17 , 31 ]. FAK overexpression in OSCC cells has been associated with histological differentiation, lymphatic metastasis, TNM stage, and is an independent prognostic factor [ 32 ]. A previous study demonstrated that knockdown of FAK in carcinoma-associated fibroblasts (CAFs) might suppress OSCC metastasis, and suggested that targeting FAK in CAFs may be a promising strategy for the OSCC treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…FAK has been verified as the target gene for several other miRs (miR-543 and miR-7) in cancer development [ 17 , 31 ]. FAK overexpression in OSCC cells has been associated with histological differentiation, lymphatic metastasis, TNM stage, and is an independent prognostic factor [ 32 ]. A previous study demonstrated that knockdown of FAK in carcinoma-associated fibroblasts (CAFs) might suppress OSCC metastasis, and suggested that targeting FAK in CAFs may be a promising strategy for the OSCC treatment [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrin-dependent FAK activation decreased cancer cells’ sensitivity to anti-EGFR drugs [10,14]. A series of studies confirmed the importance of FAK signaling in resistance to first- (erlotinib), second- (afatinib) and third-generation (osimertinib) EGFR TKIs [28,29,30,31].…”
Section: β1 Integrinsmentioning
confidence: 99%
“…Having observed that the inhibition of SRC/FAK signaling in H358-S and other NSCLC cells leads to decreased invasive ability, we sought to study the effects of these inhibitors on erlotinib sensitivity of smoke-exposed cells. In a recent study, combinatorial treatment of FAK inhibitor and erlotinib have shown synergistic effect in reducing cell viability in EGFR-TKI-resistant NSCLC cell lines [ 48 ]. H358-S, H1299 and H1650 cells were treated with varying concentration of erlotinib (0.5 µM, 1 µM and 3 µM) alone or in combination with either SRC inhibitor, dasatanib (50 nM) or FAK inhibitor, PF-562271 (4 µM) (Figure 5A-D ).…”
Section: Resultsmentioning
confidence: 99%
“…Emerging studies have shown FAK as potential cancer target in multiple cancer types [ 69 - 71 ] and phase I/II clinical trial outcomes of FAK inhibitors are awaited [ 72 ]. A recent study reported higher efficacy and synergistic effects of FAK inhibitor when used in combination with erlotinib using in-vitro and in-vivo experiments [ 48 ]. The SRC-3Delta4, a SRC3 splicing isoform is known to mediate the interaction of FAK with EGFR in mammals [ 73 ].…”
Section: Discussionmentioning
confidence: 99%